2014
DOI: 10.1534/genetics.114.172841
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Tuning of Histone H3 Lys4 Methylation During Pseudohyphal Differentiation by the CDK Submodule of RNA Polymerase II

Abstract: Transcriptional regulation is dependent upon the interactions between the RNA pol II holoenzyme complex and chromatin. RNA pol II is part of a highly conserved multiprotein complex that includes the core mediator and CDK8 subcomplex. In Saccharomyces cerevisiae, the CDK8 subcomplex, composed of Ssn2p, Ssn3p, Ssn8p, and Srb8p, is thought to play important roles in mediating transcriptional control of stress-responsive genes. Also central to transcriptional control are histone post-translational modifications. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 142 publications
3
22
0
Order By: Relevance
“…SAM is known to function as a methyl donor, and therefore it may affect methylation of DNA, histones, or other proteins that may result in the yeast-to-hypha transition. Whereas for C. albicans there are few data, for S. cerevisiae results have been obtained that clearly link histone methylation with pseudohyphal growth (52). Previously, we showed that methionine is a strong inducer of morphogenesis (38).…”
Section: Discussionmentioning
confidence: 99%
“…SAM is known to function as a methyl donor, and therefore it may affect methylation of DNA, histones, or other proteins that may result in the yeast-to-hypha transition. Whereas for C. albicans there are few data, for S. cerevisiae results have been obtained that clearly link histone methylation with pseudohyphal growth (52). Previously, we showed that methionine is a strong inducer of morphogenesis (38).…”
Section: Discussionmentioning
confidence: 99%
“…Cells deleted of the Mediator Kinase inhibitory sub-complex are pseudo-hyphal and flocculate when growing in liquid media (Hengartner et al, 1995; Holstege et al, 1998). This phenotype is reverted by deleting components of the Mediator tail or head sub-complexes (Gonzalez et al, 2014; Jeronimo et al, 2016; Law et al, 2015; Palecek et al, 2000; van de Peppel et al, 2005)(Figure 4A, Figure S4A). We therefore asked whether protein burden similarly reverts the flocculation phenotype of kinase-deleted cells.…”
Section: Resultsmentioning
confidence: 99%
“…The HAT Gcn5 has been reported to negatively regulate ICR1 expression, thereby promoting FLO11 transcriptional activation [85], most likely through regulation of a second ncRNA. Additionally, deletion of the demethylase JHD2 or a component of the CDK8 submodule of RNA pol II, SSN8 , results in elevated H3K4me3 near the FLO11 transcription start site (TSS) and constitutive activation of FLO11 [86]. These data suggest a direct role for H3K4me3 in FLO11 activation, although its potential contribution to lncRNA-dependent regulation of FLO11 has not yet been investigated.…”
Section: Nutrient-responsive Signaling and Chromatin Statesmentioning
confidence: 99%